Praktik Sosial dalam Arena Derma (Charity) Model Kopi Dindiang di Kota Padang - Meri Sutra; Damsar Damsar; Azwar Azwar (Jurnal Sosiologi Andalas, 2021)
Charity activities are usually implemented in the form of giving and sharing to others for help reduce social problems. In Padang, West Sumatra there is a sharing movement known as Kopi Dindiang (KD). The purpose of this study was to describe social practices in the arena of sharing (charity) type Kopi Dindiang in the Padang city. This Study uses a qualitative approach to the type of descriptive and informants using purposive sampling techniques. In analysing this research the writer uses social practice theory from Pierre Felix Bourdieu which discuss several concepts namely habit, field and capital with the formula (habit x capital) + Field = social practice, and data collection techniques through interviews and observations. The results of this study indicate that the habit and capital owned by agents do not always determine the success of a field. The proof is that social practices in the field of type Kopi Dindiang have decreased in existence due to several constraints from donors and outlet owners. such as causes of inactivity of Kopi Dindiang outlets which also relates to the structure that has been determined, as 3 less active and 5 the causes of inactivity of Kopi Dindiang donors. While the authors found 7 of habit from donors and owners of Kopi Dindiang outlets.